Oxidative Chemical Vapor Deposition of Neutral Hole Transporting Polymer for Enhanced Solar Cell Efficiency and Lifetime. Issue 30 (11th May 2016) - Jo, Won Jun; Nelson, Justin T.; Chang, Sehoon; Bulović, Vladimir; Gradečak, Silvija; Strano, Michael S.; Gleason, Karen K.
Abstract : The concept of a neutral hole‐transporting polymer is realized for the first time, by integrating patterned Cl − ‐doped poly(3, 4‐dimethoxythiophene) thin films into organic solar cells through a vacuum‐based polymer vapor printing technique. Due to this novel polymer's neutrality, high transparency, good conductivity, and appropriate energy levels, the solar‐cell efficiency and lifetime are significantly enhanced.